Morphological aspects of adults of Astylus variegatus (Germar, 1824) (Coleoptera, Melyridae) - Souza, Brígida; Carvalho, César Freire (Pesquisa Agropecuaria Brasileira, 1994)
A description of the external morphology of adults of Astylus variegatus (Germar, 1824) is presented. Larvae of this specie have underground behaviour and cause damage to seeds before germination. Corn seeds are the most attacked. The description of the adults may prevent crop damage due to larvae infestation by identification of adult populations, found feeding in wild or cultivated flowers. This is the first record of A. variegatus attacking corn and potato crops cultivated in rotation system in Brazil.